(3GdQCj GdYGe hCKQg aj WQjbI hVY GdOSGJjQ (B/s - (3jhSa eMehO UHMs; (3YHO GdMejO ceGd MTjTs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B:s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 1981)
(3JTJed gPg GdQSGdI Ydi bSejf; GdbSe GdChd jJfGhd GdQCj GdYGe hJWhQg GdJGQjNj, hGdbSe GdKGfj jJfGhd CKQ GdQCj GdYGe Ydi WQb hVY GdOSGJjQs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B1981. s
(3HHdjhLQGajG(B: (3UaMGJ (B333-356.s
Keywords: (3GdQCj GdYGes; (3GdJWhQ GdJGQjNj ddQCj GdYGes; (3JbSjeGJ GdQCj GdYGes; (3YhGed GdJCKjQ Ydi GdQCj GdYGes; (3WQb bjGS GdQCj GdYGes; (3CKQ GdQCj GdYGe Ydi WQjbI GdefMIs; (3CKQ GdQCj GdYGe Ydi WQjbI GdYbO aj hVY GdOSGJjQs; (3GdQCj GdYGes; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 1981